Personnel Management System in Healthcare Institutions: Foreign and Domestic Experience - Nataliia Slatvytska; Iuliia Myroshnychenko; Iana Kobushko; Ihor Rekunenko (Health Economics and Management Review)
The primary role in the organisation of healthcare facilities belongs to the medical worker, and the development of an effective personnel management system is the main task of personnel management managers in this field. The current health care system in Ukraine faces the difficult task of adapting to market conditions of business through systematic restructuring and improvement of its state regulation mechanisms, and most importantly, implementation of the integrated development and management of medical personnel, on which the performance of the system’s tasks depends. The article aims to compare the personnel management system in healthcare institutions, considering foreign and domestic experience. In addition, the authors carried out a scientific and theoretical justification of the place and role of personnel management in the healthcare field in the current conditions of the European integration of Ukraine. Within the framework of this study, the authors investigated the directions of scientific publications devoted to personnel management systems in the healthcare field. Data containing bibliographic information about scientific publications in peer-reviewed publications were obtained from the Scopus database. The results showed that scholars research human resources management in healthcare institutions, mainly focusing on personnel development, HRM, total quality management, organisational culture, personal loyalty, leadership, gender issues, and psychological aspects. The analysis of the experience of European countries with a developed healthcare system allows us to conclude that there is a need to implement optimal mechanisms for the development of human resources aimed at training, support, preservation and effective use of available resources, which is one of the important areas of personnel management of the institution. In addition, the reform strategy emphasises the need for cross-sectoral linkages (between education, health, labour and finance sectors), practical analytical justification and alignment of political decisions between sectors of the economy.